KONTESTASI PENDIDIKAN TRADISIONAL (PESANTREN) DALAM PENINGKATAN PEMAHAMAN KEISLAMAN - Syafrawi, Syafrawi (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2014)
Traditional education is the same with education of Pesantren who is executed by informal education through approach of takhassus, while senior santries who are assumed competent to science, hence they have been given by special education which is then focussed to assist them to teach. Traditional education can comprehend nature of conservative thing or maintain old ones without accepting things which in character newly. This Traditional education only see past history as something or inspiration that must be defended. Theology root of idea of the traditional human being have to accept all plans and rule of God which have been formed previously. As for science concept in Islam perspective come from God. If there are differences between empiric-realm with apocalypse, hence thinker of Islam will be more trusted and authority specification of truth and apocalypse then become a result, because truth of apocalypse considered to be absolute and real truth. Despitefully, Classic Islam look into knowledge as intact something, inwrought, and drowned, so that it forms a harmony.